Konsep Imān dalam Al-Qur’ān: Kajian Semantik Raghib al-Aṣfahānī dan Toshihiko Izutsu - Rizal Maulana; Ghozi Mubarok (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
This article examines the concept of faith (iman) in the Qur'an through a semantic approach by comparing the views of Toshihiko Izutsu and al-Raghib al-Asfahani. Faith, as one of the main pillars of Islam, is an essential component reflecting a Muslim's profound belief in God and His teachings. Utilizing semantic analysis, this study aims to delve deeper into the meaning of faith and its contrasts with other concepts in the Qur'an, such as disbelief (kufr), which is often juxtaposed with faith. By exploring the differences between Izutsu's analytical and systematic approach and al-Asfahani's classical methodology, this study provides an in-depth perspective on the structure of faith's meaning and its theological context in Islam. The findings indicate that both Izutsu's and al-Asfahani's approaches offer significant contributions to a comprehensive understanding of faith, encompassing not only belief in the heart but also verbal expressions and actions that reflect such belief. In addition, this study also highlights the importance of a semantic approach in understanding religious texts to deconstruct a more comprehensive understanding of basic concepts in Islam.